2020
DOI: 10.3390/nu12092891
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Genotype–Diet Interactions and Weight Loss—A Systematic Review

Abstract: Studies on the interactions between single nucleotide polymorphisms (SNPs) and macronutrient consumption on weight loss are rare and heterogeneous. This review aimed to conduct a systematic literature search to investigate genotype–diet interactions on weight loss. Four databases were searched with keywords on genetics, nutrition, and weight loss (PROSPERO: CRD42019139571). Articles in languages other than English and trials investigating special groups (e.g., pregnant women, people with severe diseases) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…These genetic loci may interact with obesity treatments and influence weight loss outcomes. Previous reviews have examined the interaction between genomic information and lifestyle interventions [8][9][10][11][12]. However, the literature on genetic factors in relation to weight loss after bariatric surgery has not been well synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…These genetic loci may interact with obesity treatments and influence weight loss outcomes. Previous reviews have examined the interaction between genomic information and lifestyle interventions [8][9][10][11][12]. However, the literature on genetic factors in relation to weight loss after bariatric surgery has not been well synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…A different and more complex approach is one that examines the effects of multiple SNPs. In a recent review [ 193 ], the interaction between 91 SNPs and the intake of fat, carbohydrates and protein on body weight loss concluded that the majority of those interactions were (NS) and thus the evidence was inconclusive. These results show once again the difficulty in finding and demonstrating the interaction between genetic variants and diet.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in sequencing technologies and bioinformatics approaches have allowed the characterization of a number of genetic variants across the human genome influencing the susceptibility of each individual to gain body weight [8]. The most commonly studied are single nucleotide polymorphisms (SNPs), whose effect is eventually dependent on interactions with obesogenic environmental factors, including nutritional features [9]. For example, using genome-wide association study (GWAS) weights of European ancestry samples, it was reported that the adoption of certain dietary patterns (namely consumption of sugar-sweetened beverages) may play a significant role in modifying the effect of genetic risk on obesity [10].…”
Section: Genetic Background Nutrition and Obesitymentioning
confidence: 99%